Normative Disharmony Regarding the Duration of Marital Conflict in Divorce Law and Its Impact on the Protection of Women - Zahrul Fatahillah; Muhajir, Muhammad; Hasanah, Uswatun (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
This study aims to analyze the normative disharmony regarding the time limit of disputes and quarrels as grounds for divorce within the Indonesian legal system, specifically between Government Regulation Number 9 of 1975, the Compilation of Islamic Law (KHI), and Supreme Court Circular Letter (SEMA) Number 1 of 2022. The inconsistency among these three regulations gives rise to practical issues in judicial proceedings, particularly in ensuring effective legal protection for women. Both the Government Regulation and the KHI do not stipulate a minimum duration of conflict as a requirement for divorce, whereas the SEMA explicitly requires that the dispute must have lasted for at least six months. This provision potentially obstructs women’s access to justice, especially in cases involving unhealthy or violent domestic circumstances. Employing a normative legal research method through statutory and conceptual approaches, this study finds that the time limit regulation in the SEMA is not aligned with the provisions set forth in the Government Regulation and the KHI. The norms within the SEMA are deemed insufficiently responsive to the legal needs of women, thereby necessitating regulatory harmonization to establish a just, adaptive legal system that guarantees equal protection in divorce cases. SEMA Number 1 of 2022 sets a six-month dispute requirement for divorce. This norm restricts judicial discretion and impedes legal protection for women, particularly victims of domestic violence. From a juridical perspective, the SEMA also exceeds its authority by regulating substantive matters without formal legislative processes. Consequently, substantive justice and human rights are at risk of being neglected. An urgent evaluation of this provision is necessary to ensure fair and responsive protection.